Neurodevelopmental Outcomes of Extremely Low Birth Weight Survivors in Johannesburg, South Africa - Tanusha D. Ramdin; Tanusha D. Ramdin; Robin T. Saggers; Robin T. Saggers; Rossella M. Bandini; Yoliswa Magadla; Yoliswa Magadla; Aripfani V. Mphaphuli; Aripfani V. Mphaphuli; Daynia E. Ballot (Frontiers Media S.A., 2022)
Background:Improved survival in extremely low birth weight infants (ELBWI) in Sub-Saharan Africa has raised the question whether these survivors have an increased chance of adverse neurodevelopmental outcomes.ObjectivesTo describe neurodevelopmental outcomes of ELBWI in a neonatal unit in South Africa.MethodsThis was a prospective follow-up study. All ELBWI who survived to discharge between 1 July 2013 and 31 December 2017 were invited to attend the clinic. Bayley Scales of Infant and Toddler Development (version III) were conducted at 9 to 12 months and 18 to 24 months.ResultsThere were 723 ELBWI admissions during the study period, 292 (40.4%) survived to hospital discharge and 85/292 (29.1%) attended the neonatal follow up clinic. The mean birth weight was 857.7 g (95% CI: 838.2-877.2) and the mean gestational age was 27.5 weeks (95% CI 27.1-27.9). None of the infants had any major complication of prematurity. A total of 76/85 (89.4%) of the infants had a Bayley-III assessment at a mean corrected age of 17.21 months (95% CI: 16.2-18.3). The mean composite scores for cognition were 98.4 (95% CI 95.1-101.7), language 89.9 (95% CI 87.3-92.5) and motor 97.6 (95% CI 94.5-100.6). All mean scores fell within the normal range, The study found 28 (36.8%) infants to be "at risk" for neurodevelopmental delay.ConclusionOur study demonstrates good neurodevelopmental outcome in a small group of surviving ELBWI, but these results must be interpreted in the context of the high mortality in this group of infants.